Perbedaan Efektifitas Pemberian Breastcare Dan Pijat Oksitosin Terhadap Kelancaran ASI Pada Ibu Nifas Di Puskesmas Halilulik Kabupaten Belu Tahun 2023 - Maria Magdalena Theofila Duka (Jurnal Ventilator, 2023)
The perperium or postpartum period begins after parturition from 6-48 hours, and from 3-28 days until it ends approximately 29-42 days after delivery. The research design is a two group pretest post test design. The population in this study were all postpartum mothers who were selected from the Halilulik Health Center in Belu Regency based on the average deliveries per month with estimated days of birth (HPL) June-July 2019 which is 75. A sample of at least 10 postpartum women is added 20% of the sample size, namely 2 to 12 to anticipate samples that drop out. The results showed that there was a significant difference in the milk production of postpartum mothers before and after oxytocin massage and breast care with a p-value of 0.000. In conclusion, oxytocin massage is more effective than breast care in increasing the milk production of postpartum mothers with a p-value of 0.000.